Modelagem da permeação de hidrogênio em membranas de paládio - Ribeiro Neto, Altamirando Colombo (2015)
Hydrogen is the most common substance on Earth and in the universe this element is the most part combined with others to form molecules such as water, oil, sugar, etc. It is widely used in industrial chemical processes and has been listed as a promising non-polluting fuel, since its burning produces only water. However, there are still uncommitted processes that enable a sustainable and economically viable production. In this scenario, the methane steam reforming stands out in hydrogen production despite using non-renewable sources. It is the main consolidated route and can be optimized by lowering the reaction temperature to achieve the same productivity compared to the conventional method and with lower energy consumption. It is possible to shift the equilibrium of the reaction towards the products, with the removal of hydrogen by means of a palladium membrane selective about only the diffusion of this substance. In this context, it is proposed to model, simulate and validate the hydrogen permeation through palladium membranes and apply this methodology to simulate a reformer with membrane. The work is split into two parts: modeling the membrane in the form of a system of nonlinear algebraic equations; and modeling an isothermal reforming reactor in the form of ordinary differential equations. For temperature operating conditions (325 to 1000 K) and partial pressure of hydrogen (1-0 atm) applied, the results of modeling the palladium membrane showed that the controlling steps in the process are diffusion to the membrane with thickness of 100 µm throughout the temperature range; resistance to external mass transfer to high temperatures for membrane thickness of 1 to 10 µm; desorption at low temperatures for all thickness analyzed. The membrane models applied to the reactor resulted in more efficient methane conversions than in a conventional reactor without the membrane and the thinner the membrane the greater the conversion. The residence time and surface area of the membrane are relevant parameters on the performance of the membrane reactor, because they influence the contact time of the reactants in the reactor and the hydrogen removal of the reaction system, respectively.